Status, Trend and Countermeasures of Development of Litchi Industry in the Mainland of China in 2022 - Wen'e QI; Houbin CHEN; Jiexin LI (Guangdong nongye kexue, 2023)
The study aims to explore the development status, trends and shortcomings of the litchi industry in the mainland of China under the new situation, and to propose corresponding countermeasures to enhance farmers' income and facilitate the high-quality development of litchi industry in the future. By using comparative analysis, the production scale and market situation of litchi in the mainland of China in 2021 and 2022 were compared, and the status and trend of industrial development were analyzed. The results showed that, in 2022, the cultivated area of litchi in the mainland of China remained basically stable at about 526 073.33 hm2; total output was 2 222 700 t, decreasing by 21.02% year-on-year but still keeping at a medium to high level; market demand continued to be strong and on the rise; import and export trade of litchi and products from January to August 2022 was US 839 700, decreasing by 20.02% year-on-year; the average yield per hectare of litchi was 5 176.65 kg, declining by 9.82% compared with that of 2021; the total output value of litchi was approximately 35.392 billion yuan with an increase of 46.52% year-on-year. Green, quality, distinctive and branded litchi industry for high quality and sustainable development, must be laid out from the perspective of the whole industry chain, good top-level design, consolidation of the institutional environment, improvement of the market demand-oriented industry chain integration system, science and technology to empower the sustainable development of the industry, enhancement of industrial development supporting services support system, and construction of industrial data integration and information sharing.